The influence of board gender diversity, cultural background, expertise, and experience on product responsibility performance and its implications for company growth: A study in 5 ASEAN countries - Bamumin, Najla; Handoyo, Sofik (Journal of Accounting Auditing and Business, 2025)
The study underscores the critical role of board characteristics in shaping product responsibility performance and, ultimately, firm growth, highlighting the nuanced dynamics within corporate governance. By leveraging data from the Refinitiv Database spanning five prominent ASEAN economies—Indonesia, Malaysia, the Philippines, Singapore, and Thailand- the research comprehensively analyzes 100 companies during 2022. Employing Structural Equation Modeling (SEM) via Smart PLS, the study presents compelling evidence that board gender diversity and expertise are pivotal factors that enhance product responsibility performance. This suggests that diverse perspectives and specialized knowledge within the boardroom can drive more responsible product strategies, fostering firm growth. Interestingly, the study finds that board cultural background and experience do not significantly influence product responsibility, pointing to the importance of specific skill sets over-generalized experience. Furthermore, the findings reveal that product responsibility performance significantly contributes to firm growth, indicating that companies prioritizing responsible production practices can achieve superior growth trajectories. Among various control variables examined, firm size emerges as a significant influencer of product responsibility performance, while social and environmental risks do not exhibit notable effects. This research advances the understanding of corporate board dynamics and emphasizes the strategic advantage of integrating diverse and skilled leadership to enhance organizational sustainability and growth.